Speaking and breathing in high respiratory drive. - Bailey, E. Fiona; Hoit, Jeannette D. (Journal of Speech, Language & Hearing Research, 2002)
Pulmonary ventilation during speech breathing reflects the sum of the airflow changes used to speak and to meet the metabolic needs of the body. Studying interactions between speaking and breathing may provide insights into the mechanisms of shared respiratory control. The purposes of this study were to determine if healthy subjects exhibit task-specific breathing behaviors in high respiratory drive and to document subjects' perceptions during breathing and speaking under these conditions. Ten men were studied in air and high CO2. Magnetometers were used to estimate lung volume, rib cage and abdomen volumes, minute volume, breathing frequency, tidal volume, inspiratory and expiratory duration, and inspiratory and expiratory flow. Subjects' perceptions were assessed informally. Results indicated that the chest wall kinematic behaviors associated with breathing and speaking in high drive were similar in pattern but differed in the magnitudes of lung volume and rib cage volume events and in inspiratory and expiratory flow. Linguistic influences remained strong, but not as strong as under normal conditions. All subjects reported a heightened sense of breathing-related discomfort during speaking as opposed to breathing in high respiratory drive. We conclude that in healthy subjects breathing behavior associated with speaking in high respiratory drive is guided continuously by shared linguistic and metabolic influences. A parallel-processing model is proposed to explain the behaviors observed. Reprinted by permission of the publisher.